From natural disaster to pandemic: A health-system pharmacy rises to the challenge. (16th May 2020) - Zuckerman, Autumn D; Patel, Pratish C; Sullivan, Mark; Potts, Amy; Knostman, Molly; Humphreys, Elizabeth; O'Neal, Michael; Bryant, Andrea; Torr, Donna K; Lobo, Bob; Peek, Grayson; Kelley, Tara; et al.
Abstract: Purpose: This report describes a health-system pharmacy's response to a natural disaster while staff members simultaneously prepared for the coronavirus disease 2019 (COVID-19) pandemic. By detailing our experience, we hope to help other institutions that are current facing or could encounter similar crises. Summary: In early March 2020, a tornado destroyed the health system's warehouse for storage of most clinical supplies, including personal protective equipment and fluids. The pharmacy purchasing team collaborated with suppliers and manufacturers to recover losses and establish alternative storage areas. Days later, the pharmacy department was forced to address the impending COVID-19 pandemic. Key elements of the COVID-19 response included reducing the potential for virus exposure for patients and staff; overcoming challenges in sourcing of staff, personal protective equipment, and medications; and changing care delivery practices to maintain high-quality patient care while maximizing social distancing. The pharmacy department also created distance learning opportunities for 70 pharmacy students on rotations. After an initial plan, ongoing needs include adjustment in patient care activities if significant staff losses occur, when and how to resume clinical activities, and how to best utilize the resources accumulated. Elements of practice changes implemented to reduce COVID-19 threats to patients and pharmacy personnel have proven beneficial and will be further evaluated for potential continuation. Conclusion: The pharmacy department's efforts to respond to a natural disaster and unprecedented pandemic have proven successful to this point and have illuminated several lessons, including the necessity of cohesive department communication, staff flexibility, prioritization of teamwork, and external collaboration.